Markets, models and planning: The Norwegian experience - Olav Bjerkholt (University of Oslo, Department of Economics, 2005)
After World War II economic policy in Europe comprised considerable elements of planning. The paper discusses how this shift was related to the conceived failure of the free enterprise economy to provide full employment in the interwar period and to the war experience. The Norwegian post-war planning had a more integrated and comprehensive character and a more structured format than in most other countries in Western Europe. Some major aspects of the Norwegian planning system and the models developed to support it are discussed, with particular emphasis on the roles played by key economists.
Keywords: A11; O21; P41; 330; Economic planning; planning models; national budgeting; Marshall Plan; Wirtschaftspolitik; Planwirtschaft; European Recovery Program; Wirtschaftsgeschichte; Norwegen